From beauty to horror, from dictatorship to resistance: the resignification of landscapes in Postcards from Brazil (Palíndromo, 2022)
The present article explores Postcards from Brazil, artwork made in 2016 by Gilvan Barreto, in which some photographs of landscapes advertised during the Brazilian civil-military dictatorship are transformed into postcards that, retailed, intends to refer to murders that happened at these portrayed places. This investigation aims to apprehend how the resignification of these images looks back into the authoritarian past to reconstruct truth and memory about dictatorial violence. For this, the paper reflects on the notion of landscape, including on its historical constitution. Then, it analyzes how the artist subverts some imagined predicates of Brazilian landscape by inscribing crimes in its space, making visible and recalling the horrors of the dictatorship, in an act of resistance that makes to honor the memory of its victims, perpetuated on the landscapes as absences.
Keywords: Photography; Landscape; Memory; Brazilian Military Dictatorship; Gilvan Barreto